Nigeria's Foreign Economic Relations (1998-2014) - T. W. Ojo; A. A. Adebayo (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
Since Nigeria gained independence, its foreign policy has been guided by the pursuit of its national interests in bilateral and multilateral relationships. This has remained a reflection of Nigeria's understanding of the external environment and internal dynamics. A government's actions that deal with security, defence, international political ties, and international economic interactions are referred to as its foreign policy as a concept. In order for sovereign states to remain relevant within the context of modern global political economy, the post-cold war international system has highlighted the convergence of sovereign states as a desirable goal. In light of this, a state's relative benefits are primarily determined by the design, focus, and execution of its economic diplomacy. Nigeria's economic diplomacy primarily aims to diversify its economic foundation, increase its global market, draw in foreign investment, and control its debt. This study basically looked at how Nigeria's economic diplomatic interactions have influenced or otherwise hindered its development goals. The research focuses on Nigeria's external trade patterns, the draw of foreign investments, foreign loans, and management of external debt. The qualitative descriptive approach of data analysis revealed that the issue of Nigeria's development has not been considerably addressed by the country's foreign economic ties.